Analisis Pembayaran dengan Sistem Bayar Kasbon di Kantin Madrasah: Studi Kasus di Labudda Ar Ridwan Bojonegoro - Al Fahmi, Moh. Dhofir Jenny (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
This study aims to analyze the practice of cash advance payments at the Labudda Ar Ridwan Bojonegoro Madrasah Canteen from a socio-economic and Islamic economic perspective. This study uses a qualitative approach with descriptive analytical methods through observation, interviews, and documentation of the canteen manager and students who use cash advances. The results show that the cash advance system is still relevant in the digital era because it offers flexibility, does not require an internet connection, and is based on social trust. The main factors contributing to cash advance use include family economic limitations, technical constraints, and financial constraints. Payment Service Providers (PSP), as well as urgent needs in the school environment. From a socio-economic perspective, the practice of cash advances has positive impacts in the form of increased social solidarity, empathy, and a sense of responsibility, although it has the potential to pose risks such as late payments and cash flow disruptions. From an Islamic economic perspective, cash advances are included in the contract of sale. Qardh hasan, which reflects ta’awun (please help), and ukhwah (brotherhood) without any element of usury. Furthermore, cash advances serve as a medium for character education by instilling the values ​​of honesty, discipline, and responsibility. The cash advance system in madrasas is a form of local adaptation to the limitations of digitalization and a reflection of local wisdom that balances traditional values ​​with the demands of modernity.